Diagnosis and prognostic value of circDLGAP4 in acute ischemic stroke and its correlation with outcomes - Bai, Ying; Ren, Hui; Zhu, Yi; Chen, Xufeng; Yang, Li; Xia, Jiangyan; Shu, Guofang; Han, Bing (Frontiers in Neurology, 2022)
Rationale and aims Circular RNAs are a subclass of noncoding RNAs in mammalian cells and highly expressed in the central nervous system. Although their physiological functions are not yet completely defined, they are thought to promise as stroke biomarkers because of their stability in peripheral blood. Sample Size Estimate: 222 participants. Methods and design The plasma of patients with acute ischemic stroke (AIS) (n = 111) and non-stroke controls (n = 111) from November 2017 to February 2019 were enrolled in our research. The expression of circDLGAP4 in plasma was evaluated using real-time PCR. Study outcomes In patients with AIS, circDLGAP4 was significantly decreased in comparison with non-stroke controls. The CircDLGAP4 level had a significant AUC of 0.7896 with 91.72% sensitivity and 64.83% specificity in diagnosing AIS. Furthermore, the circDLGAP4 level was related to smoking history and previous transient ischemic attack/stroke/myocardial infarction in all samples. The change rate in circDLGAP4 within the first 7 days showed an AUC curve of 0.960 in predicting an stroke outcome. Conclusion circDLGAP4 could serve as biomarker for AIS diagnosis and prediction of stroke outcomes.